2010
DOI: 10.1128/jvi.00769-10
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Lipid/DNA Complex-Adjuvanted Influenza A Virus Vaccination Induces Robust Cross-Protective Immunity

Abstract: Influenza A virus is a negative-strand segmented RNA virus in which antigenically distinct viral subtypes are defined by the hemagglutinin (HA) and neuraminidase (NA) major viral surface proteins. An ideal inactivated vaccine for influenza A virus would induce not only highly robust strain-specific humoral and T-cell immune responses but also cross-protective immunity in which an immune response to antigens from a particular viral subtype (e.g., H3N2) would protect against other viral subtypes (e.g., H1N1). Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 70 publications
1
24
0
Order By: Relevance
“…An influenza A virus vaccine adjuvanted with CLDC or alum was tested by Hong and colleagues. CLDC induced more robust adaptive immune responses with higher levels of virus-specific IgG2a/c and CD4 + and CD8 + T cells plus cross protection from lethal viral challenges [Hong et al 2010]. In another influenza A vaccine study, Dong and colleagues showed that addition of CLDC (JVRS-100) to a H5N1 split vaccine induced higher virus-specific responses than adjuvant-free formulations.…”
Section: Cationic Liposome Adjuvant Vaccinesmentioning
confidence: 97%
“…An influenza A virus vaccine adjuvanted with CLDC or alum was tested by Hong and colleagues. CLDC induced more robust adaptive immune responses with higher levels of virus-specific IgG2a/c and CD4 + and CD8 + T cells plus cross protection from lethal viral challenges [Hong et al 2010]. In another influenza A vaccine study, Dong and colleagues showed that addition of CLDC (JVRS-100) to a H5N1 split vaccine induced higher virus-specific responses than adjuvant-free formulations.…”
Section: Cationic Liposome Adjuvant Vaccinesmentioning
confidence: 97%
“…Furthermore, JVRS-100 adjuvanted inactivated influenza H1N1 vaccine provided significant cross-protection from heterosubtypic H3N2 challenges in mice (Hong et al, 2010). Both cellular and antibody-mediated immunity likely played a role in such cross-protection from antigenically distinct influenza viruses (Hong et al, 2010; Lay et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, JVRS-100 adjuvanted inactivated influenza H1N1 vaccine provided significant cross-protection from heterosubtypic H3N2 challenges in mice (Hong et al, 2010). Both cellular and antibody-mediated immunity likely played a role in such cross-protection from antigenically distinct influenza viruses (Hong et al, 2010; Lay et al, 2009). Occasionally, seasonal influenza vaccine antigens are antigenically drifted from circulating viruses which may in some cases lead to lower vaccine effectiveness (Flannery et al, 2015; Klimov et al, 1999; McNeil et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations